2019
DOI: 10.1007/jhep09(2019)061
|View full text |Cite
|
Sign up to set email alerts
|

The cosmic Galois group and extended Steinmann relations for planar $$ \mathcal{N} $$ = 4 SYM amplitudes

Abstract: We describe the minimal space of polylogarithmic functions that is required to express the six-particle amplitude in planar N = 4 super-Yang-Mills theory through six and seven loops, in the NMHV and MHV sectors respectively. This space respects a set of extended Steinmann relations that restrict the iterated discontinuity structure of the amplitude, as well as a cosmic Galois coaction principle that constrains the functions and the transcendental numbers that can appear in the amplitude at special kinematic po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
211
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(247 citation statements)
references
References 123 publications
4
211
0
1
Order By: Relevance
“…On the other hand, just as the momentum twistor space [21], G(4, n), is crucial for the amplituhedron reformulation [22,23] of all-loop integrand in planar N = 4 SYM [24], the space G + (4, n)/T can play a crucial role for all-loop integrated amplitudes (or even non-perturbatively). Recall that for n = 6, 7, all evidence so far [25][26][27][28][29][30][31] is consistent with the conjecture that the alphabet for symbol letters consists of the 9 and 42 cluster variables associated with G + (4, n)/T , respectively; it is thus highly desirable to study the structure of G + (4, n)/T for n ≥ 8. In [12,16,17], it has been shown that polytopes P(4, n) and the associated tropical positive Grassmannian indeed have intriguing applications to the mathematical structures of multi-loop scattering amplitudes in N = 4 SYM.…”
Section: Introductionsupporting
confidence: 53%
“…On the other hand, just as the momentum twistor space [21], G(4, n), is crucial for the amplituhedron reformulation [22,23] of all-loop integrand in planar N = 4 SYM [24], the space G + (4, n)/T can play a crucial role for all-loop integrated amplitudes (or even non-perturbatively). Recall that for n = 6, 7, all evidence so far [25][26][27][28][29][30][31] is consistent with the conjecture that the alphabet for symbol letters consists of the 9 and 42 cluster variables associated with G + (4, n)/T , respectively; it is thus highly desirable to study the structure of G + (4, n)/T for n ≥ 8. In [12,16,17], it has been shown that polytopes P(4, n) and the associated tropical positive Grassmannian indeed have intriguing applications to the mathematical structures of multi-loop scattering amplitudes in N = 4 SYM.…”
Section: Introductionsupporting
confidence: 53%
“…with ρ = ρ(g 2 ) a function of the coupling constant. This function was determined iteratively in [13,33] by demanding that the spaces of functions in which the perturbative amplitudes live obey a coaction principle associated to a cosmic Galois group [48][49][50]. The implementation of this requirement fixes ρ order by order in perturbation theory, ln ρ = 8ζ 2 3 g 6 − 160ζ 3 ζ 5 g 8 + 16(−2ζ 4 ζ 2 3 + 57ζ 2 5 + 105ζ 3 ζ 7 )g 10 + .…”
Section: Cosmic Normalizationmentioning
confidence: 99%
“…Intriguingly, one of the anomalous dimensions also appears in the light-like limit of the octagon [27][28][29][30][31][32], a correlation function of four operators with large R charge. We also predict the nonlogarithmic term, as well as the coefficient ρ controlling a "cosmic" amplitude normalization [33]. More precisely, we consider the MHV amplitude normalized by the BDS-like ansatz [11,12,34,35], which remains finite as the dimensional regulator = 2− 1 2 D → 0, E(u i ) = lim →0 A 6 (s ij , ) A BDS-like 6 (s ij , ) = exp R 6 + 1 4 Γ cusp E (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Feynman) diagrammatic expansion. Examples of such triumphs include the recent determination of certain six-particle amplitudes in planar maximally supersymmetric (N =4) Yang-Mills theory (sYM) through seven loops [21][22][23][24][25][26][27][28][29], and through four loops for seven particles [30][31][32].…”
Section: Introductionmentioning
confidence: 99%